The Effectiveness of using the Hijaiyah Game within the Natural Method to enhance writing skills - Hilira, Anggini Putri; Kasmiati, Kasmiati; Halomoan, Halomoan; Syaf, Moh. Najib (Jurnal Kawakib, 2024)
It was experiment research aiming at finding out the effectiveness of Natural method with Hijaiyah game in increasing student writing ability at the fourth grade of Islamic Integrated Elementary School of An-Najiyah. The formulation of the problem in this research was "was Natural method with Hijaiyah game to increase student writing ability at the fourth grade of Islamic Integrated Elementary School of An-Najiyah Pekanbaru?". All the fourth-grade students at Islamic Integrated Elementary School of An-Najiyah Pekanbaru were the population of this research, and the samples were the fourth-grade students of class A as the experiment group and the students of class B as the control group. Observation, test, and documentation were the instruments of collecting data. Based on data analysis, it could be concluded that Natural method with Hijaiyah game was effective in increasing student writing ability at the fourth grade of Islamic Integrated Elementary School of An-Najiyah Pekanbaru because the result of student dimensional test showed that the score of fobserved was 1.475 at t tailed 38, and the score 0.232 was higher than 5% significant level (0.232>0.05). Besides, the experiment group was used, and mean score of Natural method was 84.50. So, Ha was accepted and Ho was rejected, if Natural method was implemented effectively to student writing ability.